Answer:
At steady state output will be 2
Step-by-step explanation:
We have given transfer function
![G(S)=(6)/(12S+3)](https://img.qammunity.org/2020/formulas/engineering/college/x2vuslephqmx8dgf1jqn42f0winjwb9772.png)
Input is unit step so
![X(S)=(1)/(S)](https://img.qammunity.org/2020/formulas/engineering/college/3k6nreqbv15m3aw1ikxty4g1n8ldlpmcbi.png)
We know that
, here
, is output
So output
![Y(S)=G(S)* X(S)](https://img.qammunity.org/2020/formulas/engineering/college/55sqrilkmyemgae91gjdv3q4fri6h138ty.png)
![Y(S)=(1)/(S)* (6)/(12S+3)](https://img.qammunity.org/2020/formulas/engineering/college/wuv5lpbw50r6vjdwn165fcqjiq7e608f97.png)
Taking 12 common from denominator
![Y(S)=(1)/(2S(S+(1)/(4)))](https://img.qammunity.org/2020/formulas/engineering/college/teh39aklbod3asbxjs985qo81kc0qzp331.png)
Now using partial fraction
![(1)/(2S(S+(1)/(4)))=(A)/(2S)+(B)/((S+(1)/(4)))](https://img.qammunity.org/2020/formulas/engineering/college/k39t858rerg1ql4444i0eyihkxwfakvt3m.png)
![(1)/(2S(S+(1)/(4)))=(A(S+(1)/(4)+2BS))/(2S(S+(1)/(4)))](https://img.qammunity.org/2020/formulas/engineering/college/r3vhxzplns48u8rxdxiikuuz0zvketp6vk.png)
![AS+(A)/(4)+2BS=1](https://img.qammunity.org/2020/formulas/engineering/college/vq9j7lrsiqken6rdaravg7h9bnl61k5o23.png)
On comparing coefficient A=4 and B = -2
Putting the values of A and B in Y(S)
![Y(S)=(4)/(2S)-(2)/(S+(1)/(4))](https://img.qammunity.org/2020/formulas/engineering/college/7bzqo33zu7vpb8ju9iwb07e7929epnk19r.png)
Now taking inverse la place
![y(t)=2-2e^{(-t)/(4)}](https://img.qammunity.org/2020/formulas/engineering/college/e3f2se5493awe59cu6e7vcwxakeo5c521m.png)
Steady state means t tends to infinite
So output at steady state =
![y(t)=2-2e^{(-\infty)/(4)}](https://img.qammunity.org/2020/formulas/engineering/college/3inbow08ftlafj8hszh32drlisu4xwiguq.png)